KAJIAN PSIKOLOGI SASTRA TEORI DAVID KRECH DALAM LAGU “SEMUA AKU DIRAYAKAN” KARYA NADIN AMIZAH - Inne Azkia Agustina; Rindiani Purnamasari (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the classification of emotions in the lyrics of the song All I Am Celebrated by Nadin Amizah. The method used by the researcher is a descriptive qualitative approach. The data in this study is in the form of words and sentences in the lyrics of the song All I Am Celebrated by Nadin Amizah. The data collection technique used to obtain data for this research is the record and listen technique. The data was analyzed based on David Krech's theory which categorized into 4 classifications of emotions, namely, (1) Basic Emotions, (2) Emotions Related to Sensory Stimulus, (3) Emotions Related to Self-Assessment, and (4) Emotions Related to Others. The results of the analysis of basic emotions included 3 data, emotions related to sensory stimulus 1 data, emotions related to self-assessment 2 data, and emotions related to others 1 data.